(untitled) (Khairulummah, 2024)
The manuscript ʿUqūd al-Durar fī Sharḥ Abīyāt al-Muṭawwal wa al-Mukhtaṣar by Ḥusain ibn Shihāb al-Dīn by the famous scholar in Syria Died 1076 A.H,the author in this book explained literary the poets of the famous two books of Arabic rhetorical-Muṭawwal wa al-Mukhtaṣar by Sa’d al-Din al-Taftazani 790 A. H. This is a critical work in Arabic rhetoric, reflecting the refined stylistic traditions of pre Islamic and classical Islamic peotry. This study examines the rhetorical styles employed in its preface, highlighting the intricate use of balāgha (eloquence) to frame the work’s intellectual and literary significance. Through an analysis of al-Maʿānī (eloquent meanings), ʿelm al-maʿānī, studying the role of syntax in literary style, It’s rules provide the foundation for the use of rhetorical embellishment this research demonstrates how the author crafts a persuasive and aesthetically rich introduction. The preface not only establishes the manuscript’s scholarly authority but also exemplifies the linguistic and stylistic conventions of classical Arabic prose. By situating these rhetorical elements within the broader tradition of Islamic literary and theological discourse, this study provides insights into the role of prefaces as both introductory frameworks and rhetorical showcases.